Pengaruh Gaya Mengajar dan Umpan Balik terhadap Hasil Belajar Passing Bawah Bola Voli - Rivianto Mandiangan; Rafli Bondi; Francien T Patras (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to examine the effect of teaching styles and feedback on students’ learning outcomes of underhand passing in volleyball. The research employed a quasi-experimental method using a 2x2 factorial design. The independent variables were teaching style (practice style and command style) and feedback (immediate feedback and delayed feedback), while the dependent variable was students’ learning outcomes of underhand passing in volleyball. The population consisted of male students of the Physical Education Coaching Department, with a total sample of 40 students selected using total sampling and randomly assigned into four experimental groups. Data were collected using a standardized volleyball underhand passing skill test and analyzed using two-way ANOVA at a significance level of α = 0.05. The results showed that students taught using the practice teaching style achieved significantly higher learning outcomes compared to those taught using the command teaching style. Immediate feedback also resulted in better learning outcomes than delayed feedback. Furthermore, there was a significant interaction between teaching style and feedback on students’ learning outcomes. These findings indicate that the selection of appropriate teaching styles combined with effective feedback strategies plays an important role in improving students’ volleyball underhand passing skills.